Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Want to score 90 percentile or higher on GMAT CR? Attend this free webinar to learn how to pre-think assumptions and solve the most challenging questions in less than 2 minutes.

Re: If 6xy = x^2*y + 9y, what is the value of xy?
[#permalink]

Show Tags

05 Jun 2013, 05:25

6

8

Manhnip wrote:

The equation in question can be rephrased as follows: x^2 y – 6xy + 9y = 0

y(x^2 –6x+9)=0

y(x–3)^2=0￼

Therefore, one or both of the following must be true: y = 0 or x=3 It follows that the product xy must equal either 0 or 3y. This question can therefore be rephrased “What is y?”

(1) INSUFFICIENT: This equation cannot be manipulated or combined with the original equation to solve directly for x or y. Instead, plug the two possible scenarios from the original equation into the equation from this statement:

If x = 3, then y = 3 + x = 3 + 3 = 6, so xy = (3)(6) = 18. If y = 0, then x = y – 3 = 0 – 3 = -3, so xy = (-3)(0) = 0. Since there are two possible answers, this statement is not sufficient.

(2) SUFFICIENT: If x3 < 0, then x < 0. Therefore, x cannot equal 3, and it follows that y = 0. Therefore, xy = 0.

Ans B

Please someone confirm on the solution, if the approach is correct

Yes, that's correct.

If 6xy = x^2y + 9y, what is the value of xy?

\(6xy=x^2y + 9y\) --> \(y(x^2-6x+9)=0\) --> \(y(x-3)^2=0\) --> either \(x=3\) or \(y=0\) (or both).

(1) y – x = 3. If \(y=0\) and \(x=-3\), then \(xy=0\) but if \(x=3\) and \(y=6\), then \(xy=18\). Not sufficient.

(2) x^3 < 0 --> \(x<0\) --> \(x\neq{3}\), then \(y=0\) and \(xy=0\). Sufficient.

Re: If 6xy = x^2*y + 9y, what is the value of xy?
[#permalink]

Show Tags

05 Jun 2013, 05:13

13

11

The equation in question can be rephrased as follows: x^2 y – 6xy + 9y = 0

y(x^2 –6x+9)=0

y(x–3)^2=0￼

Therefore, one or both of the following must be true: y = 0 or x=3 It follows that the product xy must equal either 0 or 3y. This question can therefore be rephrased “What is y?”

(1) INSUFFICIENT: This equation cannot be manipulated or combined with the original equation to solve directly for x or y. Instead, plug the two possible scenarios from the original equation into the equation from this statement:

If x = 3, then y = 3 + x = 3 + 3 = 6, so xy = (3)(6) = 18. If y = 0, then x = y – 3 = 0 – 3 = -3, so xy = (-3)(0) = 0. Since there are two possible answers, this statement is not sufficient.

(2) SUFFICIENT: If x3 < 0, then x < 0. Therefore, x cannot equal 3, and it follows that y = 0. Therefore, xy = 0.

Ans B

Please someone confirm on the solution, if the approach is correct

Re: If 6xy = x^2*y + 9y, what is the value of xy?
[#permalink]

Show Tags

06 Jul 2014, 07:34

Bunuel wrote:

Manhnip wrote:

The equation in question can be rephrased as follows: x^2 y – 6xy + 9y = 0

y(x^2 –6x+9)=0

y(x–3)^2=0￼

Therefore, one or both of the following must be true: y = 0 or x=3 It follows that the product xy must equal either 0 or 3y. This question can therefore be rephrased “What is y?”

(1) INSUFFICIENT: This equation cannot be manipulated or combined with the original equation to solve directly for x or y. Instead, plug the two possible scenarios from the original equation into the equation from this statement:

If x = 3, then y = 3 + x = 3 + 3 = 6, so xy = (3)(6) = 18. If y = 0, then x = y – 3 = 0 – 3 = -3, so xy = (-3)(0) = 0. Since there are two possible answers, this statement is not sufficient.

(2) SUFFICIENT: If x3 < 0, then x < 0. Therefore, x cannot equal 3, and it follows that y = 0. Therefore, xy = 0.

Ans B

Please someone confirm on the solution, if the approach is correct

Yes, that's correct.

If 6xy = x^2y + 9y, what is the value of xy?

\(6xy=x^2y + 9y\) --> \(y(x^2-6x+9)=0\) --> \(y(x-3)^2=0\) --> either \(x=3\) or \(y=0\) (or both).

(1) y – x = 3. If \(y=0\) and \(x=-3\), then \(xy=0\) but if \(x=3\) and \(y=6\), then \(xy=18\). Not sufficient.

(2) x^3 < 0 --> \(x<0\) --> \(x\neq{3}\), then \(y=0\) and \(xy=0\). Sufficient.

Aaah this formatting.. I read the stem as x^(2y) and was totally stuck. Can this ambiguity in notation come in actual test ? I would have expected a bracket or at the least correct ordering like 6xy = yx^2

Re: If 6xy = x^2*y + 9y, what is the value of xy?
[#permalink]

Show Tags

06 Jul 2014, 11:12

himanshujovi wrote:

Bunuel wrote:

Manhnip wrote:

The equation in question can be rephrased as follows: x^2 y – 6xy + 9y = 0

y(x^2 –6x+9)=0

y(x–3)^2=0￼

Therefore, one or both of the following must be true: y = 0 or x=3 It follows that the product xy must equal either 0 or 3y. This question can therefore be rephrased “What is y?”

(1) INSUFFICIENT: This equation cannot be manipulated or combined with the original equation to solve directly for x or y. Instead, plug the two possible scenarios from the original equation into the equation from this statement:

If x = 3, then y = 3 + x = 3 + 3 = 6, so xy = (3)(6) = 18. If y = 0, then x = y – 3 = 0 – 3 = -3, so xy = (-3)(0) = 0. Since there are two possible answers, this statement is not sufficient.

(2) SUFFICIENT: If x3 < 0, then x < 0. Therefore, x cannot equal 3, and it follows that y = 0. Therefore, xy = 0.

Ans B

Please someone confirm on the solution, if the approach is correct

Yes, that's correct.

If 6xy = x^2y + 9y, what is the value of xy?

\(6xy=x^2y + 9y\) --> \(y(x^2-6x+9)=0\) --> \(y(x-3)^2=0\) --> either \(x=3\) or \(y=0\) (or both).

(1) y – x = 3. If \(y=0\) and \(x=-3\), then \(xy=0\) but if \(x=3\) and \(y=6\), then \(xy=18\). Not sufficient.

(2) x^3 < 0 --> \(x<0\) --> \(x\neq{3}\), then \(y=0\) and \(xy=0\). Sufficient.

Aaah this formatting.. I read the stem as x^(2y) and was totally stuck. Can this ambiguity in notation come in actual test ? I would have expected a bracket or at the least correct ordering like 6xy = yx^2

Edited the original post to avoid such confusions in future.

By the way x^2y means x^2*y. If it were \(x^{2y}\) it would be written x^(2y). But don't worry on the actual test the formatting will be clearer.

Re: If 6xy = x^2*y + 9y, what is the value of xy?
[#permalink]

Show Tags

06 Jul 2014, 21:23

Bunnuel,

Why is it wrong to divide the original equation by y? Since dividing the equation by y gives you x^2-6x+9=0 which gives you x=3, then statement 1 is sufficient to give you the value of y and therefore give you the value of xy as 18.

Statement 2 is not consistent with the original equation as it shows x^3<0 which is not possible (x=3, so 3^3=27) and is therefore insufficient. Therefore, answer should be A.

Or is it that only because statement 2 is inconsistent with the original equation and therefore we need to try a different approach?

Re: If 6xy = x^2*y + 9y, what is the value of xy?
[#permalink]

Show Tags

07 Jul 2014, 01:06

3

ravih wrote:

Bunnuel,

Why is it wrong to divide the original equation by y? Since dividing the equation by y gives you x^2-6x+9=0 which gives you x=3, then statement 1 is sufficient to give you the value of y and therefore give you the value of xy as 18.

Statement 2 is not consistent with the original equation as it shows x^3<0 which is not possible (x=3, so 3^3=27) and is therefore insufficient. Therefore, answer should be A.

Or is it that only because statement 2 is inconsistent with the original equation and therefore we need to try a different approach?

If you divide (reduce) 6xy = x^2*y + 9y by y, you assume, with no ground for it, that y does not equal to zero thus exclude a possible solution (notice that both y = 0 AND x = 3 satisfy the equation).

Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We can not divide by zero. _________________

Re: If 6xy = x^2*y + 9y, what is the value of xy?
[#permalink]

Show Tags

06 May 2015, 01:22

Dear Bunuel, Thanks for the bringing out such fundamental issues.

Re: If 6xy = x^2*y + 9y, what is the value of xy?

I made the same error: jumped to eliminate y from LHS & RHS > came up with x=3, then solved for y as given in condition 1 to arrive at xy=18 hence right answer = A

Per your explanation: If you divide (reduce) 6xy = x^2*y + 9y by y, you assume, with no ground for it, that y does not equal to zero thus exclude a possible solution (notice that both y = 0 AND x = 3 satisfy the equation).

Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We can not divide by zero.

It makes absolute sense and I feel like I am on a totally different wavelength and am solving the problems inconsistently very consistently! This is in-spite of the detailed guides and theoretical resources provided here. Is this just a matter of practice and training one's brain to approach a problem in a more ordered fashion or something fundamentally amiss?

Re: If 6xy = x^2*y + 9y, what is the value of xy?
[#permalink]

Show Tags

06 May 2015, 02:15

rohitd80 wrote:

Dear Bunuel, Thanks for the bringing out such fundamental issues.

Re: If 6xy = x^2*y + 9y, what is the value of xy?

I made the same error: jumped to eliminate y from LHS & RHS > came up with x=3, then solved for y as given in condition 1 to arrive at xy=18 hence right answer = A

Per your explanation: If you divide (reduce) 6xy = x^2*y + 9y by y, you assume, with no ground for it, that y does not equal to zero thus exclude a possible solution (notice that both y = 0 AND x = 3 satisfy the equation).

Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We can not divide by zero.

It makes absolute sense and I feel like I am on a totally different wavelength and am solving the problems inconsistently very consistently! This is in-spite of the detailed guides and theoretical resources provided here. Is this just a matter of practice and training one's brain to approach a problem in a more ordered fashion or something fundamentally amiss?

Yes, I think practicing similar algebra/inequality questions should help.
_________________

If 6xy = x^2*y + 9y, what is the value of xy?
[#permalink]

Show Tags

09 Nov 2015, 01:46

Bunuel, I did but there is some minor point that I am just not getting. For instance: if x3 < 0 i.e. x is negative, how do we know that y will be 0? I am not following how either the original equation - y(x+3)^2 =0 - or the above solutions are leading us to this conclusion. thanks a ton

Re: If 6xy = x^2*y + 9y, what is the value of xy?
[#permalink]

Show Tags

09 Nov 2015, 01:50

1

mais1990 wrote:

Bunuel, I did but there is some minor point that I am just not getting. For instance: if x3 < 0 i.e. x is negative, how do we know that y will be 0? I am not following how either the original equation - y(x+3)^2 =0 - or the above solutions are leading us to this conclusion. thanks a ton

For y(x−3)^2 to be 0, either x must be 3 or y must be 0 (or both). x^3 < 0 implies that x is NOT 3, thus y MUST be 0 (in order y(x−3)^2 to be 0).
_________________

Re: If 6xy = x^2*y + 9y, what is the value of xy?
[#permalink]

Show Tags

09 Nov 2015, 03:53

Bunuel wrote:

mais1990 wrote:

Bunuel, I did but there is some minor point that I am just not getting. For instance: if x3 < 0 i.e. x is negative, how do we know that y will be 0? I am not following how either the original equation - y(x+3)^2 =0 - or the above solutions are leading us to this conclusion. thanks a ton

For y(x−3)^2 to be 0, either x must be 3 or y must be 0 (or both). x^3 < 0 implies that x is NOT 3, thus y MUST be 0 (in order y(x−3)^2 to be 0).

Re: If 6xy = x^2*y + 9y, what is the value of xy?
[#permalink]

Show Tags

10 Nov 2015, 11:39

Forget conventional ways of solving math questions. In DS, Variable approach is the easiest and quickest way to find the answer without actually solving the problem. Remember equal number of variables and independent equations ensures a solution.

If 6xy = x^2*y + 9y, what is the value of xy?

(1) y – x = 3

(2) x^3 < 0

If we modify the question, 0=x^2*y-6xy+9y, or 0=y(x^2-6x+9), or 0=y(x-3)^2, and we want to know whether y=0 or x=3. There are 2 variables (x,y) and 1 equation (0=x^2*y-6xy+9y). 2 more equations are given from the 2 conditions, so there is high chance (D) will be our answer. From condition 1, y=0 and x=-3 or x=3 and y=6. This is not sufficient as this is not unique. From condition 2, x^3<0--> x<0. But x=3>0, and y has to be y=0, and xy=0, so the condition is sufficient; the answer is (B).

For cases where we need 1 more equation, such as original conditions with “1 variable”, or “2 variables and 1 equation”, or “3 variables and 2 equations”, we have 1 equation each in both 1) and 2). Therefore, there is 59 % chance that D is the answer, while A or B has 38% chance and C or E has 3% chance. Since D is most likely to be the answer using 1) and 2) separately according to DS definition. Obviously there may be cases where the answer is A, B, C or E.
_________________

If 6xy = x^2*y + 9y, what is the value of xy?
[#permalink]

Show Tags

05 Oct 2018, 04:43

The equation in question can be rephrased as follows: x2y – 6xy + 9y = 0 y(x2 – 6x + 9) = 0 y(x – 3)2 = 0 Therefore, one or both of the following must be true: y = 0 or x = 3 It follows that the product xy must equal either 0 or 3y. This question can therefore be rephrased “What is y?”

1) INSUFFICIENT: This equation cannot be manipulated or combined with the original equation to solve directly for x or y. Instead, plug the two possible scenarios from the original equation into the equation from this statement: If x = 3, then y = 3 + x = 3 + 3 = 6, so xy = (3)(6) = 18. If y = 0, then x = y – 3 = 0 – 3 = -3, so xy = (-3)(0) = 0. Since there are two possible answers, this statement is not sufficient. (2) SUFFICIENT: If x3 < 0, then x < 0. Therefore, x cannot equal 3, and it follows that y = 0. Therefore, xy = 0. The correct answer is B.

Re: If 6xy = x^2*y + 9y, what is the value of xy?
[#permalink]

Show Tags

09 Oct 2018, 05:31

ArvGMAT wrote:

If 6xy = x^2*y + 9y, what is the value of xy?

(1) y – x = 3

(2) x^3 < 0

This video is not only the video solution of this question, but also an explanation how the DS questions should be approached.

It also highlights a common mistake of many test takers

_________________

Prosper!!! GMATinsight Bhoopendra Singh and Dr.Sushma Jha e-mail: info@GMATinsight.com I Call us : +91-9999687183 / 9891333772 Online One-on-One Skype based classes and Classroom Coaching in South and West Delhi http://www.GMATinsight.com/testimonials.html

Re: If 6xy = x^2y + 9y, what is the value of xy? (1) y x = 3 (2)
[#permalink]

Show Tags

01 Oct 2019, 04:13

Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________